Adverse selection in an insurance market with government-guaranteed subsistence levels - Bum J. Kim; Harris Schlesinger (Center for Economic Studies and ifo Institute (CESifo), 2004)
We consider a competitive insurance market with adverse selection. Unlike the standard models, we assume that individuals receive the benefit of some type of potential government assistance that guarantees them a minimum level of wealth. For example, this assistance might be some type of government-sponsored relief program, or it might simply be some type of limited liability afforded via bankruptcy laws. Government assistance is calculated ex post of any insurance benefits. This alters the individuals? demand for insurance coverage. In turn, this affects equilibria in various insurance models of markets with adverse selection.
Keywords: D82; H29; G22; 330; adverse selection; insurance; government relief; Versicherungsökonomik; Adverse Selection; Subvention; Theorie